Two new species of Limonium (Plumbaginaceae) from Rhodes Island (eastern Aegean area, Greece) - Crespo, Manuel B.; Pena-Martín, Carolina (Phytotaxa, 2013)
Limonium quinnii and L. rhodense (Plumbaginaceae) are here described from the maritime cliffs of Rhodes Island (Greece). These new species can be included in the Limonium palmare aggregate, a group highly diversified in the eastern Mediterranean but still poorly known. The differences among L. quinnii and L. rhodense with the related taxa are provided and discussed. Data on the breeding systems, ecology and distribution of both species are also given.